S-Nitrosylation-Mediated Reduction of Ca(V)1.2 Surface Expression and Open Probability Underlies Attenuated Vasoconstriction Induced by Nitric Oxide - Hu, Zhenyu (LIPPINCOTT WILLIAMS & WILKINS, 2023)
10.1161/HYPERTENSIONAHA.122.19103